PELATIHAN KORESPONDENSI DALAM BAHASA INGGRIS UNTUK STAF BAGIAN PEMERINTAHAN DI PEMERINTAHAN KOTA BATU - Hilda Cahyani; Nadia Hanayeen; Prima Beauty Kartikasari (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P2M) IKIP Budi Utomo Malang, 2022)
This PKM aims to provide correspondence skills in English. Currently the need for communication in English is a necessity. This training involved staff from the Government Section in the Batu City administration who had several times received offers to work with foreign parties and overseas industries. Data collection techniques in this PKM are through observation, providing training, and conducting evaluations. During the training, participants showed active participation and had seriousness, willingness and high motivation to write correspondence. The training process (final writing training) provides benefits for staff, namely it can increase staff understanding of, foster motivation in writing correspondence, and carry out correspondence as well as for agencies can improve government performance. The results of this activity can be used as input for other department offices in an effort to improve the quality of staff and also cooperate with foreign parties for the development of networks and cooperation.